2015
DOI: 10.1159/000381423
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis from Laboratory to Bedside: The Role of A20 in NF-κB-Mediated Inflammation

Abstract: Cystic fibrosis (CF) is a lifelong, inflammatory multi-organ disease and the most common lethal, genetic condition in Caucasian populations, with a median survival rate of 41.5 years. Pulmonary disease, characterized by infective exacerbations, bronchiectasis and increasing airway insufficiency is the most serious manifestation of this disease process, currently responsible for over 80% of CF deaths. Chronic dysregulation of the innate immune and host inflammatory response has been proposed as a mechanism cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 81 publications
(110 reference statements)
1
12
0
Order By: Relevance
“…Obesity is a low-grade chronic proinflammatory state, identified by enhances in serum levels of various chemokines, cytokines, and soluble cytokine receptors, and results in airway inflammation and asthma severity [27] . Previous reports have indicated that NF-κB has an important role in allergic inflammation of airways [28] . A study conducted by Poynter et al [5] showed that rapid and selective activation of NF-κB occurred in mice airway epithelium challenged and sensitized with antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a low-grade chronic proinflammatory state, identified by enhances in serum levels of various chemokines, cytokines, and soluble cytokine receptors, and results in airway inflammation and asthma severity [27] . Previous reports have indicated that NF-κB has an important role in allergic inflammation of airways [28] . A study conducted by Poynter et al [5] showed that rapid and selective activation of NF-κB occurred in mice airway epithelium challenged and sensitized with antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Similar approaches might also be fruitful for studies of other signaling molecules from plants and phytopathogenic fungi that have been found to show pharmacological effects in animals, like for example gibberellins (Hedden and Thomas, 2012; Annand et al, 2015; Bannon et al, 2015; Reihill et al, 2016) and SA (Klessig et al, 2016). Since no genes are known that regulate intracellular ABA homeostasis in animals, utilizing proteins and pathways known in plants and phytopathogenic fungi could help defining the physiological role of ABA in animals.…”
Section: Perspectives: How Plant Science and Studies Of Phytopathogenmentioning
confidence: 99%
“…NF- κ B pathway is an important signal pathway in inflammatory process (Bannon et al. 2015 ). SSa attenuates inflammation mainly by inhibiting the activation of NF- κ B pathway (Wu et al.…”
Section: Ssamentioning
confidence: 99%